Low-temperature sintering aluminum paste for forming PTC (Positive Temperature Coefficient) thermistor aluminum electrode and preparation method of low-temperature sintering aluminum paste

Through low-melting point alloy aluminum paste without glass powder, combined with low-temperature sintering technology, the electrical performance deviation and welding performance problems caused by glass powder in traditional aluminum paste are solved, and higher conductivity and better welding performance are achieved.

CN119541922AActive Publication Date: 2025-02-28SHENZHEN SENLONT ELECTRONICS
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411615774.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-28
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The addition of glass powder in traditional PTC thermistor aluminum paste will lead to changes in matrix component distribution, deviation of electrical performance index, reduced volume conductivity and adverse effects on surface silver paste, affecting the matching and welding performance of the electrodes.

Method used

Low-melting point alloy aluminum paste without glass powder is used to form low-melting point alloy components by matching different metals in a certain proportion, and a dense electrode layer is formed with aluminum powder particles, and the formation of electrodes is achieved by low-temperature sintering technology.

Benefits of technology

The adverse effects of glass powder on the matrix and surface silver paste during sintering are solved, the conductivity and adhesion of the aluminum electrode are improved, and the matching and welding performance with the silver paste are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005132178530000051
    Figure BDA0005132178530000051
  • Figure BDA0005132178530000052
    Figure BDA0005132178530000052
  • Figure BDA0005132178530000061
    Figure BDA0005132178530000061
Patent Text Reader

Abstract

The invention discloses low-temperature sintering aluminum paste for forming an aluminum electrode of a PTC (Positive Temperature Coefficient) thermistor and a preparation method, relates to the field of conductor paste, and aims to overcome the defects caused by using glass powder in a traditional preparation method, different metals are matched according to a certain proportion to form a low-melting-point alloy component, and the low-melting-point alloy component is matched with aluminum powder particles to form a compact electrode layer. And glass powder is abandoned. The aluminum paste provided by the invention can realize good metallization at 450-600 DEG C, forms good ohmic contact and mechanical combination with a PTC substrate, and improves the conductivity of an electrode layer. Meanwhile, the pressure-sensitive silver paste can also be used on a pressure-sensitive resistor element to form an ohmic contact electrode, after sintering at 500-600 DEG C, good ohmic contact and adhesive force can also be formed, and the electrical performance and the aging performance of current universal pressure-sensitive silver paste and copper paste are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of conductor paste, and in particular to a low-temperature sintered aluminum paste for forming an aluminum electrode of a PTC thermistor and a preparation method thereof. Background Art

[0002] PTC (positive temperature coefficient) thermistor is a special resistor whose resistance value increases with the increase of temperature. Utilizing its unique temperature sensitivity, the resistance value can be changed according to the change of temperature, so it is widely used in overcurrent protection, overheat protection, temperature measurement and control, etc. At present, the electrode materials of PTC thermistor mainly include ohmic silver-zinc paste, electroplated nickel electrode, ohmic aluminum paste and other forms. Ohmic silver-zinc paste generally contains 30-50% silver and the rest is zinc, which has a high cost. As the market is sensitive to cost, silver-zinc paste is slowly being replaced by aluminum paste; electroplated nickel electrode involves huge equipment investment and environmental protection issues, and the technical advantage is also shrinking. The cost advantage of ohmic aluminum paste is obvious. The raw material supply chain including glass powder and aluminum powder has become more and more perfect thanks to the huge development of solar aluminum paste, and its market share is also increasing.

[0003] The traditional aluminum paste used as the electrode of PTC thermistor is mainly composed of metal aluminum powder, glass powder and organic carrier. The aluminum paste is mixed under the action of mechanical force, and then screen-printed onto the ceramic substrate. After high-temperature sintering, the aluminum electrode is obtained. The organic carrier can adjust the viscosity and process thixotropy of the paste, which is conducive to screen printing and forming electrodes. During the high-temperature sintering process, the organic carrier is heated and volatilized and decomposed to separate from the paste system. As the temperature rises, the glass powder gradually melts and penetrates and infiltrates the PTC substrate. At the same time, the aluminum powder is bonded to the substrate in the liquid glass to form an electrode. The aluminum powders are in effective contact with each other and play a conductive role.

[0004] Glass powder is a key material in traditional aluminum paste. It is made of a series of oxides through high-temperature melting, quenching and ball milling to obtain ultra-fine glass powder. While it acts as a binder in aluminum paste, as its application deepens, glass powder also brings some negative effects to aluminum paste. One is that the glass powder will penetrate into the interior of the PTC ceramic substrate during the sintering process of the aluminum paste, thereby changing the overall component distribution of the ceramic substrate, causing the PTC ceramic to fail to achieve the designed electrical properties, such as increasing the dispersion of resistance values, and fluctuating. Another is that the addition of glass powder reduces the volume conductivity of the aluminum paste. In addition, most PTC thermistors that require welding leads need to print and burn a layer of surface silver paste. The glass powder in the aluminum paste will also have an adverse effect on the silver paste layer. When the silver paste is sintered, the glass powder in the aluminum paste will react with the silver paste and transition to the silver paste layer, making the silver paste and the aluminum electrode layer poorly matched, and will also affect the appearance and welding performance of the silver paste. Summary of the invention

[0005] In view of the above problems, the ohmic aluminum paste described in this application abandons the traditional glass powder, uses different metals in a certain proportion to form a low melting point alloy component, and forms a dense electrode layer with aluminum powder particles. The present invention adopts the following technical solutions:

[0006] The present invention provides a low-temperature sintered aluminum paste for forming an aluminum electrode of a PTC thermistor. The aluminum paste comprises metal powder (accounting for 70-90% by mass of the paste), an organic additive (accounting for 0.1-4.0% by mass of the paste), a resin (accounting for 0.5%-5.0% by mass of the paste), and a solvent (accounting for 5%-25% by mass of the paste).

[0007] The characteristic that distinguishes it from traditional ohmic aluminum paste is that it does not contain glass-based inorganic binders composed of glass powder or oxides, which solves the problems of changes in the designed electrical performance indicators, decreased conductivity of aluminum electrodes, and impact on printed silver electrodes caused by the penetration of glass powder into the substrate during sintering.

[0008] The metal powder includes:

[0009] Aluminum powder (35-80 wt % of metal powder), zinc powder (5-40 wt % of metal powder) and

[0010] Nickel powder (accounting for 2-20wt% of metal powder) three kinds of metal powder;

[0011] And at least one of the following metal powders:

[0012] Bismuth powder (accounting for 0-20wt% of metal powder), magnesium powder (accounting for 0-20wt% of metal powder),

[0013] Iron powder (accounting for 0-20wt% of metal powder), ruthenium powder (accounting for 0-20wt% of metal powder), indium powder (accounting for 0-20wt% of metal powder), manganese powder (accounting for 0-20wt% of metal powder), titanium powder (accounting for 0-20wt% of metal powder), silver powder (accounting for 0-20wt% of metal powder), gold powder (accounting for 0-20wt% of metal powder), lead powder (accounting for 0-10wt% of metal powder), vanadium powder (accounting for 0-10wt% of metal powder) and / or alloy powder (accounting for 0-30wt% of metal powder);

[0014] The alloy powder refers to the pre-made alloy powder 1 and / or alloy powder 2, wherein the alloy powder 1 is a mixture of one or more of aluminum-copper alloy powder (copper accounts for 30-40wt% of the alloy powder), aluminum-magnesium alloy (magnesium accounts for 40-70wt% of the alloy powder), aluminum-zinc alloy powder (zinc accounts for 80-95wt% of the alloy powder), and silver-bismuth alloy powder (bismuth accounts for 20-30wt% of the alloy powder), and the alloy powder 2 is an alloy powder composed of aluminum and one or more non-metallic elements of silicon, boron, sulfur, and phosphorus, wherein aluminum accounts for 85-99wt% and the rest are non-metallic elements. If the mixing ratio of alloy powder 1 to alloy powder 2 is 1:4-4:1.

[0015] The preparation method of alloy powder generally adopts the conventional atomization method. First, various metal and non-metal elements are weighed according to the proportion. The whole process is protected by nitrogen atmosphere, heated to molten metal liquid, and then sprayed with high-pressure nitrogen to form tiny metal droplets. After the droplets are cooled, atomized metal alloy powder is obtained. By adjusting the spray process parameters, powders of different particle sizes can be obtained. Subsequently, classification treatment will be carried out to obtain alloy powder of ideal particle size.

[0016] The addition of alloy powder allows the alloy powder and low-temperature metal powder to be pre-melted during the sintering process, so that the unmelted metal powder particles are infiltrated and shrunk, filling the space left by the volatilization of organic matter, making it easier for the powder particles to contact and penetrate each other, forming an ideal alloy structure. At the same time, the alloy powder can also control and guide the low-temperature metal and other metals to form a specific alloy composition and crystal structure, increasing the density of the film layer and the adhesion to the ceramic matrix.

[0017] The morphology and particle size of the powder can be refined as follows: aluminum powder is spherical, flake or branched with a D50 of 0.5-5.0 microns; zinc powder is spherical, flake or branched with a D50 of 0.5-5.0 microns; nickel powder is spherical, flake or branched with a D50 of 0.1-0.5 microns; other pure metal powders and alloy powders are spherical with a D50 of 0.5-2.5 microns. The oxygen content of all metal powders and alloy powders ranges from 0-10000ppm.

[0018] The organic additive is one or more of an organic silicon additive (BYK-3451, BYK-3456, BYK-348, BYK-349), an organic boron additive (triethanolamine borate, tributyl borate, tripropyl borate), an organic acid tin (dimethyltin, dibutyltin, dizinc-based tin, stannous octoate), an organic acid titanium (tetrabutyl titanate, tetraethyl titanate, tetraisopropyl titanate), an organic acid bismuth (bismuth isooctanoate, bismuth laurate, bismuth neodecanoate, bismuth cyclohexane), and an organic acid zinc (zinc isooctanoate, zinc stearate, zinc formate, zinc acetate).

[0019] Organic additives provide printing performance support, which is beneficial to promote film formation and drying adhesion. At the same time, they decompose into corresponding metal oxides during the formation process of metal electrodes (sintering process) to improve the density and electrical properties of the electrodes.

[0020] The resin is a mixture of two or more of ethyl cellulose, hydroxyethyl cellulose, polymethyl methacrylate, polyvinyl acetate, and styrene-maleic anhydride copolymer resin.

[0021] The solvent is a mixed solvent consisting of two or more of terpineol, cyclohexane, diethylene glycol ethyl ether acetate, glycol diacetate and propylene glycol methyl ether acetate.

[0022] The present invention also provides a method for preparing a low-temperature sintered aluminum paste for forming an aluminum electrode of a PTC thermistor, wherein the method comprises the following steps:

[0023] 1) Weigh various metal powders, organic additives, resins, solvents and other materials according to the proportion, mix them in a kneader, and then pass through a three-roll mill to fully disperse them;

[0024] 2) The obtained material is placed in a vacuum stainless steel sealed container and aged at 80-100°C for 48-168 hours, and then stirred again to obtain the low-temperature sintered aluminum slurry. A certain period of aging ensures sufficient infiltration between the powder and the organic carrier, reduces the activity of the metal powder, and ensures the stability of the fluidity and viscosity of the subsequent slurry.

[0025] The aluminum paste provided by the present invention can achieve good metallization at 450-600°C, form good ohmic contact and mechanical bonding with the PTC substrate, and improve the conductivity of the electrode layer. At the same time, it can also be used to form ohmic contact electrodes on varistor elements. After sintering at 500-600°C, it can also form good ohmic contact and adhesion, and achieve the electrical properties and aging properties of the currently common varistor silver paste and copper paste. DETAILED DESCRIPTION

[0026] First, various metal powders, organic additives, resins, solvents and other materials are weighed according to the formula ratio, mixed in a kneader for 1-5 hours, and then rolled in a three-roll mill for 1 hour to fully disperse. The obtained slurry is placed in a vacuum stainless steel sealed container and aged at 80-100°C for 48-168 hours, and then stirred again to obtain the low-temperature sintered aluminum slurry.

[0027] The present invention has a total of 8 embodiments, and the specific proportions of each embodiment are shown in Table 1 below:

[0028]

[0029] The composition of the metal powder in each embodiment (mass percentage of the total metal powder) is:

[0030]

[0031]

[0032] The composition of the organic additives in each embodiment (mass percentage of the slurry) is:

[0033]

[0034]

[0035] The composition of the resin in each embodiment (mass percentage of the slurry) is:

[0036]

[0037] The composition of the solvent in each embodiment (mass percentage of the slurry) is:

[0038]

[0039]

[0040] The different ohmic aluminum pastes obtained in Examples 1-8 are respectively printed on the front and back sides of several PTC thermistor substrates by screen printing (provided by a well-known domestic PTC thermistor component manufacturer, with a resistance of 2.0-3.0Ω), dried at 120°C, and sintered in a box furnace (560°C for 10 minutes). Several PTC thermistor substrates with sintered aluminum electrodes are obtained. The resistance of each substrate at 25°C is measured with a multimeter to obtain the resistance R1. Take 10 substrates, grind off the aluminum electrodes with sandpaper, apply indium gallium electrodes, measure their resistance at 25°C, and obtain their body resistance R. Take another 10 substrates with fired aluminum electrodes, print silver paste (existing products of Shenglongte Company, trade name SK-5570), and dry, sinter (540°C for 10 minutes), measure their resistance at 25°C, and obtain the resistance R2 after silver firing.

[0041] The following test instructions:

[0042] 1) Aluminum electrode square resistance test: the test process is in accordance with the national standard GB / T1747.3-2008 "Test method for precious metal paste for microelectronics technology - square resistance determination", and the film thickness is 20 microns.

[0043] 2) The change rate of the resistance value of the PTC thermistor after sintering the aluminum electrode = [(R1-R) / R]*100%

[0044] 3) The resistance range of the PTC thermistor after sintering the aluminum electrode = R1 最大值 -R1 最小值

[0045] 4) After sintering the silver electrode, the change rate of the resistance value of the PTC thermistor = [(R2-R1) / R1]*100%

[0046] 5) After sintering the silver electrode, the resistance value of the PTC thermistor is as follows: R2 maximum value - R2 minimum value

[0047] 6) The resistance change rate after 30 days of storage at room temperature is the resistance change rate of the silver-sintered substrate after 30 days of storage in a room temperature warehouse under natural conditions. The resistance change rate after 30 days of storage = [(R2(30 days)-R2) / R2]*100%.

[0048] 7) The on-off test is to simulate the actual use conditions of the PTC thermistor substrate and detect its stability and reliability. First, 20 substrates with burned silver electrodes are clamped with two electrodes of the substrate and fixed on the testing machine. Under a voltage of 24V, one cycle is made up of 3 seconds on and 60 seconds off. After 10,000 on-off test cycles, the resistance value of the substrate is measured to be R3, and the resistance value change rate = [(R3-R2) / R2]*100%.

[0049] Square resistance of aluminum electrode mΩ / □ (electrode film thickness 20μm)

[0050] Example 1 2 3 4 5 6 7 Comparison 1 15 15 13 12.5 12 10 10.8 25

[0051] Glass powder is added to Comparative Example 1, and its sheet resistance is higher than that of Example 1. Compared with Comparative Example 1, the conductivity of Examples 1-7 is improved.

[0052] The change rate of the resistance value of the PTC thermistor after sintering the aluminum electrode

[0053] Example 1 2 3 4 5 6 7 Comparison 1 2.56% 2.50% 2.26% 2.05 1.89% 1.05% 1.15% 3.50%

[0054] The resistance value range of PTC thermistor after sintering aluminum electrode (Ω)

[0055] Example 1 2 3 4 5 6 7 Comparison 1 0.62 0.58 0.59 0.55 0.6 0.56 0.57 1.51

[0056] The change rate of the resistance value of the PTC thermistor after sintering the silver electrode

[0057] Example 1 2 3 4 5 6 7 Comparison 1 1.50% 1.34% 1.25% 1.10% 1.15% 1.02% 1.08% 2.45%

[0058] The resistance value range of PTC thermistor after sintering silver electrode (Ω)

[0059] Example 1 2 3 4 5 6 7 Comparison 1 0.63 0.58 0.58 0.57 0.6 0.56 0.57 1.75

[0060] Secondly, due to the influence of the glass powder on the substrate and the surface silver layer during the sintering process, the change rate of the resistance value of Comparative Example 1 is larger than that of Examples 1-7, and the range difference of the resistance value after aluminum sintering and silver sintering is also significantly larger, and the dispersion of the resistance value is obvious. In particular, the range difference and change rate of the resistance value after silver sintering are significantly larger in Comparative Example 1 than in Examples 1-7, indicating that the matching of the aluminum electrode and the silver electrode in Examples 1-7 is better than that in Comparative Example 1.

[0061] Resistance change rate after storage at room temperature for 30 days

[0062] Example 1 2 3 4 5 6 7 Comparison 1 2.74% 2.72% 2.66% 2.34% 2.51% 1.79% 1.85% 2.76%

[0063] Resistance change rate in on-off test (10,000 on-off tests, 24V, on for 3 seconds and off for 60 seconds)

[0064] Example 1 2 3 4 5 6 7 Comparison 1 2.52% 3.05% 2.98% 2.67% 2.56% 2.43% 2.40% 5.67%

[0065] Furthermore, the storage stability of comparative example 1 is similar to that of example 1, but the on-off test results show that the stability of its resistance value under simulated use conditions is worse than that of the examples without glass powder. Moreover, comparing the on-off test results of examples 1, 6, and 7 that also do not contain glass powder but contain alloy powder with those of examples 2, 3, 4, and 5 that do not contain alloy powder, the resistance change rate of examples 1, 6, and 7 is smaller than that of examples 2, 3, 4, and 5. The addition of prefabricated alloy powder has the effect of increasing the density of the film layer.

[0066] Solderability test and determination

[0067] The substrate with the silver electrode burn-infiltration completed is inserted into the lead wire (0.6mm tinned copper wire) on the wiring board, dipped in the flux, and then the entire sample is immersed in a lead-free solder tin bath (solder material Sn96.5Ag3) set at a temperature of 245±3℃ for 3±0.3 seconds. The solderability inspection should be carried out under sufficient lighting conditions with a 4╳ to 25╳ magnifying glass. The silver-brushed surface of the immersed workpiece should be completely covered by the relevant solder material, without pinholes, non-wetting or excessive wetting. The coverage rate is greater than 95% and the surface is smooth and bright, which means good solderability. The coverage rate is 85%-95% and the tin layer is smooth, which means general solderability. The coverage rate is less than 80%, and the tin layer is not smooth and dark, which means poor solderability. The test results of the embodiments and comparative examples are shown in the following table.

[0068] Adhesion test

[0069] Use the clamps of the tensile testing machine to clamp the leads of the wafer resistor after welding, start the tensile testing machine, and pull the leads in opposite directions. When the leads are pulled away from the substrate, the maximum tensile force value is recorded as the adhesion value. The test results of the embodiments and comparative examples are shown in the following table.

[0070]

[0071] Due to the influence of glass powder, the welding performance of comparative example 1 (containing glass powder) is worse than that of examples 1-7. Although the adhesion is basically at the same level, the minimum adhesion value of examples 1-7 is greater than that of comparative example 1, which also shows that the aluminum electrode without glass powder has better matching with silver paste than the aluminum electrode with glass powder. In addition, comparing the adhesion results of examples 1-7 containing alloy powder and examples 2, 3, 4, 5 without alloy powder, which also do not contain glass powder, the adhesion of examples 1, 6, 7 is greater than that of examples 2, 3, 4, 5, whether the maximum value or the minimum value, which proves that the addition of prefabricated alloy powder has the effect of increasing the density of the film layer and the adhesion to the substrate.

Claims

1. A low temperature sintered aluminum paste for forming aluminum electrodes of a PTC thermistor, characterized in that: The aluminum paste comprises 70-90% by mass of metal powder, 0.1-4.0% by mass of organic additives and 0.5-5.0% by mass of resin, and the rest is solvent.

2. The low temperature sintered aluminum paste for forming an aluminum electrode of a PTC thermistor according to claim 1, characterized in that: The metal powder includes: The first component: the first component comprises 35-80wt% of aluminum powder, 5-40wt% of zinc powder and 2-20wt% of nickel powder; and The second component includes at least one of bismuth powder, magnesium powder, iron powder, ruthenium powder, indium powder, manganese powder, titanium powder, silver powder and gold powder accounting for 0-20wt% of the total weight of the metal powder, lead powder and vanadium powder accounting for 0-10wt% of the total weight of the metal powder, and alloy powder accounting for 0-30wt% of the total weight of the metal powder; The alloy powder in the second component is one or more of the prefabricated alloy powder 1 or alloy powder 2, wherein the alloy powder 1 is a mixture of one or more of an aluminum-copper alloy powder in which copper accounts for 30-40wt%, an aluminum-magnesium alloy in which magnesium accounts for 40-70wt%, an aluminum-zinc alloy powder in which zinc accounts for 80-95wt%, and a silver-bismuth alloy powder in which bismuth accounts for 20-30wt%. The alloy powder 2 is an alloy powder composed of aluminum and one or more of the non-metallic elements silicon, boron, sulfur, and phosphorus. The aluminum in the alloy powder 2 accounts for 85-99wt%, and the rest is non-metallic elements.

3. The low temperature sintered aluminum paste for forming an aluminum electrode of a PTC thermistor according to claim 2, characterized in that: The alloy powder is made of alloy powder 1 and alloy powder 2 in a mixing ratio of 1:4-4:

1.

4. The low temperature sintered aluminum paste for forming an aluminum electrode of a PTC thermistor according to claim 2, characterized in that: The aluminum powder is a spherical, flaky or dendritic powder with a D50 of 0.5-5.0 microns, the zinc powder is a spherical, flaky or dendritic powder with a D50 of 0.5-5.0 microns, the nickel powder is a spherical, flaky or dendritic powder with a D50 of 0.1-0.5 microns, other metal powders and alloy powders are spherical powders with a D50 of 0.5-2.5 microns, and the oxygen content of all metal powders and alloy powders ranges from 0 to 10000 ppm.

5. The low temperature sintered aluminum paste for forming an aluminum electrode of a PTC thermistor according to claim 1, characterized in that: The organic auxiliary agent is one or more of an organic silicon auxiliary agent, an organic boron auxiliary agent, an organic acid tin, an organic acid titanium, an organic acid bismuth and an organic acid zinc.

6. The low temperature sintered aluminum paste for forming an aluminum electrode of a PTC thermistor according to claim 5, characterized in that: The organosilicon additive is one or more of BYK-3451, BYK-3456, BYK-348 and BYK-349; or, The organic boron auxiliary agent is one or more of triethanolamine borate, tributyl borate and tripropyl borate; or, The organic acid tin is one or more of dimethyltin, dibutyltin, dizinctin and stannous octoate; or, the organic acid titanium is one or more of tetrabutyl titanate, tetraethyl titanate and tetraisopropyl titanate; or, the organic acid bismuth is one or more of bismuth isooctanoate, bismuth laurate, bismuth neodecanoate and bismuth cyclohexane; or, the organic acid zinc is one or more of zinc isooctanoate, zinc stearate, zinc formate and zinc acetate.

7. The low temperature sintered aluminum paste for forming an aluminum electrode of a PTC thermistor according to claim 1, characterized in that: The resin is a mixture of two or more of ethyl cellulose, hydroxyethyl cellulose, polymethyl methacrylate, polyvinyl acetate, and styrene-maleic anhydride copolymer resin.

8. The low temperature sintered aluminum paste for forming aluminum electrodes of a PTC thermistor according to claim 1, characterized in that: The solvent is a mixed solvent consisting of two or more of terpineol, cyclohexane, diethylene glycol ethyl ether acetate, glycol diacetate and propylene glycol methyl ether acetate.

9. The method for preparing a low-temperature sintered aluminum paste for forming an aluminum electrode of a PTC thermistor according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: 1) Prepare the materials according to the proportion, mix them in a kneader, and then disperse them evenly through a three-roll mill; 2) The obtained material is placed in a vacuum sealed stainless steel container and aged at 80-100° C. for 48-168 hours, and then stirred again to obtain the low-temperature sintered aluminum slurry.

Citation Information

Patent Citations

  • Lead-free conducting resin and manufacture method thereof

    CN102646458A

  • Solar cell aluminum electric-conduction slurry and preparation method thereof

    CN103165214A

  • Electrode slurry composition of solar cell

    CN103295660A

  • Alloy powder for silicon solar cell aluminum paste

    CN103617820A

  • Positive silver paste and preparation method thereof

    CN107068241A